A novel monogenic preimplantation genetic testing strategy for sporadic polycystic kidney caused by de novoPKD1 mutation. Issue 2 (20th November 2020) - Shi, Hao; Niu, Wenbin; Liu, Yidong; Jin, Haixia; Song, Wenyan; Shi, Senlin; Yao, Guidong; Xu, Jiawei; Sun, Yingpu
Abstract: Autosomal dominant hereditary polycystic kidney disease (ADPKD) is the most common inherited kidney disease that causes end‐stage renal disease and kidney failure. Preimplantation genetic testing for monogenic (PGT‐M) can effectively prevent the transmission of genetic diseases from parents to the offspring before pregnancy. However, PGT‐M currently adopts the single nucleotide polymorphism (SNP) linkage analysis for embryo's pathogenic gene carrying status and linkage analysis requires proband of the family. Here we report a new PGT‐M strategy using single sperm SNP linkage analysis for male patient with sporadic ADPKD caused by de novo PKD1 mutation. We recruited five couples with male patient with ADPKD caused by de novo PKD1 mutation, and 39 embryos from six PGT‐M cycles were detected. The five couples had at least one embryo that does not carry the PKD1 mutation. Within these five couples, the accuracy of carrier status of embryos was confirmed by amniotic fluid gene detection of two couples and two couples successfully delivered healthy fetuses. Therefore, the new PGT‐M strategy of using single sperm SNP linkage analysis was proved to be feasible and effective for male patient with ADPKD caused by de novo PKD1 mutation. Abstract : Autosomal dominant hereditary polycystic kidney disease (ADPKD) is the most common inherited kidney disease that causes end‐stage renal disease and kidney failure. Preimplantation genetic testing for monogenic (PGT‐M) can effectively prevent the transmission of genetic diseases from parents to the offspring before pregnancy. However, PGT‐M currently adopts the single nucleotide polymorphism (SNP) linkage analysis for embryo's pathogenic gene carrying status and linkage analysis requires proband of the family. Here we report a new PGT‐M strategy using single sperm SNP linkage analysis for male patient with sporadic ADPKD caused by de novo PKD1 mutation. The workflow of new PGT‐M strategy is shown in Figure 1. First, we perform whole genome amplification (WGA) of a single sperm and Sanger sequencing was applied to detect the mutation. Second, biopsied TE cells from embryo were subjected to WGA and the next‐generation sequencing (NGS) was applied to detect aneuploidy of embryo. Subsequently, the SNPs flanking the mutation were examined for all the embryos, the couples and single sperm by NGS. According to the carrying state of the mutation of single sperm, linkage analysis was carried out to identify the male haplotype of carrying the mutation. Finally, by comparing with the haplotype of carrying the mutation, the carrier status of mutation of the embryo was deduced. In this study, we recruited five couples with male patient with ADPKD caused by de novo PKD1 mutation, and 39 embryos from six PGT‐M cycles were detected. Within these five couples, the accuracy of carrier status of embryos was confirmed by amniotic fluid gene detection of two couples and two couples successfully delivered healthy fetuses. Therefore, the new PGT‐M strategy of using single sperm SNP linkage analysis was proved to be feasible and effective for male patient with ADPKD caused by de novo PKD1 mutation.